The macrobenthic infauna of Tolo Harbour and Tolo Channel , Hong Kong. - Shin, Paul K. S. ([Edited book chapter. Workshop proceedings], 1982)
The macrobenthic infauna of Tolo Harbour and Tolo Channel, Hong Kong was surveyed using a 0.05 m2 vrn Veen grab at twenty-three sampling locations. Fortyseven species of macrobenthic animals were recorded and of these, thirty-four species were polychaetous annelids. A few species were found to be abundant, particularly in the harbour proper. Based on the faunal similarity, six station groups were separated. In addition, species characterizing these station groups were identified. The zonation of macrobenthic assemblages and the possible role of the benthos as indicators of environmental perturbations in the study area are briefly discussed .
Annelidabase. Not known to be online except here at WoRMS